2005
DOI: 10.1196/annals.1327.083
|View full text |Cite
|
Sign up to set email alerts
|

Sea Bream (Sparus auratus) Estrogen Receptors: Phylogeny and Tissue Distribution

Abstract: Most estrogen actions are mediated by two estrogen receptor subtypes (ERalpha and ERbeta). While a single ERbeta appears to be present in higher vertebrates, two forms of ERbeta encoded by different genes have recently been isolated in some teleost fish species. We investigated whether this also applies to the hermaphrodite sparid sea bream (Sparus auratus) and cloned a second ERbeta (sbERbeta2) in this species. We have also compared the tissue distribution of the three receptors as yet identified in sea bream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Therefore, the hypercalcemic effect of E 2 can be either mediated directly through its action in the gills or intestine, indirectly via another endocrine factor responsive to E 2 , or both. Support for direct estrogen effects come from the presence of ER mRNA in fish gills (9,19) and intestine (4,9,45), including in the sea bream (33,35,41). However, in the present study we also show that a large part of the E 2 -induced hypercalcemia is largely indirect possibly via PTHrP or a related factor.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, the hypercalcemic effect of E 2 can be either mediated directly through its action in the gills or intestine, indirectly via another endocrine factor responsive to E 2 , or both. Support for direct estrogen effects come from the presence of ER mRNA in fish gills (9,19) and intestine (4,9,45), including in the sea bream (33,35,41). However, in the present study we also show that a large part of the E 2 -induced hypercalcemia is largely indirect possibly via PTHrP or a related factor.…”
Section: Discussionsupporting
confidence: 61%
“…pengze, Pcc) (Zheng et al, 2013); so that these species have four different ERs isotypes, two ERα and two ERβ. In the gilthead seabream, an important Mediterranean aquaculture species in which our group has carried out numerous studies, ERα, ERβ1 and ERβ2 have been identified and seen to be expressed in both reproductive and non-reproductive organs such as liver, brain, heart, kidney, intestine, gills, muscle and skin (Pinto et al, 2005).…”
Section: Ers In Fishmentioning
confidence: 99%
“…(described by Bulder et al [31]) were partly E 2 -like (feminization of F 1 and VTG induction, but only in females) and partly TMX-like (decreased egg production and adult gonad histopathology, including asynchronous maturation within spermatogenic cysts, TMX-like oocyte atresia, folding of oocyte membranes, and hypertrophy of granulosa cells). This paradox suggests that complex mixtures of estrogen-active compounds may elicit effects that differ from those evoked by the individual compounds, possibly because of diverging, interacting mechanisms of these compounds at the various estrogen receptors, which have a differential expression between different target tissues [34,35].…”
Section: Application Of the Protocolmentioning
confidence: 99%